2021
DOI: 10.1097/md.0000000000028251
|View full text |Cite
|
Sign up to set email alerts
|

Febrile episode unmasking neuropsychiatric systemic lupus erythematosus with lytic lesions caused by secondary autoimmune myelofibrosis

Abstract: Rationale: Systemic lupus erythematosus (SLE) is characterized by numerous immunological abnormalities that lead to multiorgan involvement. Central and peripheral nervous system manifestations are present in 8% to 92% of the cases of SLE. Furthermore, there have been reported cases of secondary autoimmune myelofibrosis associated with SLE. Patient concerns: We present the case of a 64-year-old female who was transferred from the Cardiology Department, where she was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The treatment of ICAD includes thrombolytic therapy, antithrombotic therapy, endovascular therapy, and surgery. [26][27][28] This case demonstrates that it is difficult to diagnose ICAD without typical clinical manifestations at an early stage, especially in the elderly. In this case, the symptoms of headache and hiccups appeared on the third day of treatment after admission, which indicated that the symptoms of ICAD may evolve and worsen gradually over a few days.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The treatment of ICAD includes thrombolytic therapy, antithrombotic therapy, endovascular therapy, and surgery. [26][27][28] This case demonstrates that it is difficult to diagnose ICAD without typical clinical manifestations at an early stage, especially in the elderly. In this case, the symptoms of headache and hiccups appeared on the third day of treatment after admission, which indicated that the symptoms of ICAD may evolve and worsen gradually over a few days.…”
Section: Discussionmentioning
confidence: 93%
“…At present, the treatment of recurrent hiccups caused by ICAD mainly focuses on the cause, that is, the treatment of ICAD. The treatment of ICAD includes thrombolytic therapy, antithrombotic therapy, endovascular therapy, and surgery 26‐28 . This case demonstrates that it is difficult to diagnose ICAD without typical clinical manifestations at an early stage, especially in the elderly.…”
Section: Discussionmentioning
confidence: 96%